2021
DOI: 10.1016/j.msard.2020.102595
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SARS-CoV2 on the anxiety levels of subjects and on the anxiety and depression levels of their parents

Abstract: Highlights SARS-CoV2 pandemic affects daily life of people, negatively. Children with MS seem to be more affected in terms of anxiety symptoms due to their susceptibility to anxiety. Establishment of separate health centers to be used during such pandemic/ epidemic periods for patients with chronic diseases such as MS may be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 11 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…All 15 cross-sectional studies reported the severity of mental health symptoms during the COVID-19 pandemic. Of these, eight (53.3%) sampled a control population to compare with PwMS ( Bonavita et al, 2020 ; Costabile et al, 2020 ; Dilek et al, 2021 ; Garjani et al, 2021 ; Motolese et al, 2020 ; Shaygannejad et al, 2021a ; Stojanov et al, 2020 ; Talaat et al, 2020 ). Two cross-sectional studies examined the mental health status of parents and caregivers of PwMS as well as PwMS ( Dilek et al, 2021 ; Talaat et al, 2020 ).All six longitudinal studies reported the severity of mental health symptoms among PwMS prior to or early in the COVID-19 pandemic along with follow-up measures in a lockdown period ( Andreu-Caravaca et al, 2021 ; Capuano et al, 2021 ; Chiaravalloti et al, 2021 ; Demir et al, 2020 ; Garjani et al, 2021 ; Stojanov et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 15 cross-sectional studies reported the severity of mental health symptoms during the COVID-19 pandemic. Of these, eight (53.3%) sampled a control population to compare with PwMS ( Bonavita et al, 2020 ; Costabile et al, 2020 ; Dilek et al, 2021 ; Garjani et al, 2021 ; Motolese et al, 2020 ; Shaygannejad et al, 2021a ; Stojanov et al, 2020 ; Talaat et al, 2020 ). Two cross-sectional studies examined the mental health status of parents and caregivers of PwMS as well as PwMS ( Dilek et al, 2021 ; Talaat et al, 2020 ).All six longitudinal studies reported the severity of mental health symptoms among PwMS prior to or early in the COVID-19 pandemic along with follow-up measures in a lockdown period ( Andreu-Caravaca et al, 2021 ; Capuano et al, 2021 ; Chiaravalloti et al, 2021 ; Demir et al, 2020 ; Garjani et al, 2021 ; Stojanov et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies (n=14) used online surveys for data collection. Four studies excluded participants with comorbid psychiatric conditions ( Altunan et al, 2021 ; Chiaravalloti et al, 2021 ; Demir et al, 2020 ; Stojanov et al, 2020 ), nine studies did not mention pre-existing psychiatric comorbidities prior to the onset of the COVID-19 outbreak ( Alschuler et al, 2021 ; Andreu-Caravaca et al, 2021 ; Bonavita et al, 2020 ; Broche-Perez et al, 2021 ; Capuano et al, 2021 ; Dilek et al, 2021 ; Naser Moghadasi, 2020 ; Shaygannejad et al, 2021b ; Talaat et al, 2020 ), and the remaining six articles reported baseline psychiatric comorbidity status ( Costabile et al, 2020 ; Garjani et al, 2021 ; Motolese et al, 2020 ; Ramezani et al, 2021 ; Shaygannejad et al, 2021a ; Zanghi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Lundberg (1998) [ 49 ], the degree of stress depends on an individual’s cognitive evaluation of danger and potential injury. Therefore, people with poorer overall health tend to consider physical symptoms catastrophically and overestimate the risk of serious diseases, which may cause higher anxiety during pandemics [ 30 , 31 , 32 ]. The results also echoed with Robinson et al’s meta-analysis of longitudinal cohort studies, revealing that when comparing mental health symptoms to pre-pandemic levels, larger rises for depressive symptoms and those with existing poor physical health may have been most affected [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For people with poor health, especially those suffering from certain diseases that have potential risks for infectious diseases due to the nature of the disease, catastrophic thinking about physical symptoms and overestimation of the risk of serious diseases may cause higher anxiety during pandemics [ 30 , 31 ]. The findings reported by Malesza and Kaczmarek (2021) also show that people with chronic diseases and poorer overall health have higher COVID-19 anxiety due to a greater perceived risk of infection [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This questionnaire was not validated because we did not have resources on COVID-19 outbreak, but was used for an earlier study conducted at our hospital. 13 We adapted this questionnaire for use with CF patients (see in Supplementary Data S2).…”
Section: Introductionmentioning
confidence: 99%